Post-Covid architectural rural social house - Manrique Niño, María Ximena (Centro Universitario de Arte, Arquitectura y Diseño, 2021)
The architectural re-invention of rural social housing in the Colombian cultural landscape, at a time in which civil society has recently faced a latent health emergency situation caused by the global pandemic by Covid-19, is a purpose that proposes the execution of strategic actions on the part of the State and operative alternatives designed integrally, proposed from the workshops and offices that the union leads, from the exercise of the discipline of architecture and its auxiliary professions. The establishment of viable project solutions for projects of architecture of rural social housing post-Covid, make necessary a special treatment of integral sustainable improvement of the habitat, both in its urban and rural component. In the case of the Colombian rural cultural landscape, the time the pandemic a ected has revealed unsustainable and uninhabitable conditions in conventional social housing prototypes, in terms of safety, health and comfort variables.  The theoretical exploration presented below re ects on the principles of sustainable and pro- ductive design of the landscape, the habitat, and the architecture of rural social housing in Colombia; said re ection describes and presents viable solutions of healthy and self sufficient design, among other attributes, applicable in the design of rural social housing projects in di erent climatic and cultural contexts; the reflection article also takes advantage of the experience of coordinating the Architect María Ximena Manrique Niño of the public contest of ideas for the de- sign of prototypes of sustainable and productive housing units for the rurality of D. C., promoted in 2018 by the Colombian Society of Sectional Architects Bogotá D. C. and Cundinamarca, and the District Planning Secretariat of the Mayor’s O ce of Bogotá D. C.